PENGARUH KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN MELALUI KINERJA PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA (BEI) - Sahrul, M; Sobri, Mohamad Aulia; Ratnawati, Tri (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2020)
The purpose of this research is to determine the effect of Investment Decision on Firm’s Value through Firm Performance. The object of this research was mining companies listed on Bursa Efek Indonesia (BEI) during 2016-2018. Firm’s value as dependent variable measured by PBV and EPS. The independent variable in this research is investment decision measured by PER and MBVA. Then, intervening variable is firm performance measured by ROA and ROE. Data analysis techniques use Partial Least Square (PLS) and from data processing and hypothesis testing, produced 3 accepted hypothesis and 1 hypothesis is rejected. The results of this study were (1) Investment decision has no effect on firm value, (2) Investment decision has positive effect on firm performance, (3) Firm performance has positive effect on firm’s value, (4) Firm performance has mediating effect on the relationship between investment decision and firm’s value.Kata Kunci : Investment Decision, Firm Performance, and Firm’s Value.